KHONDAMIR'S «NAMA-I-NAMI» IS AN IMPORTANT SOURCE ON THE CULTURAL HISTORY OF CENTRAL ASIA, IRAN AND AFGHANISTAN OF THE XV–XVI CENTURIES (Scientific journal of the Fergana State University, 2023)
The article introduces into scientific circulation some of the letters contained in the little-known work of Khondamir «Nama-i-nami».